UNDERAGE MARRIAGE IN THE PERSPECTIVE OF WOMEN'S PROTECTION - Widihartati S; Khudzaifah Dimyati; Absori Absori; Aidul Fitriciada Azhari (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2017)
Underage marriage is marriage committed by underage children or adolescents in which it must obtain the permission from the Judges of the Religious Court. This study aims at describing and exploring underage marriage dispensations based on the decision of the religious court judges in the Province of Central Java. This research uses juridical-normative method with qualitative and descriptive research type. The data of this research is secondary data that are related directly to the research object. Technique of collecting data is literature study, i.e. various main and supporting materials related to the problem. Data analysis techniques are processed and discussed using deductive methods. The results of the research indicate that the judges' ruling only concerns with the doctrine of positive law with the aim at obtaining clear legal status. Therefore, their decision does not take intoaccount the aspects of the future interests of children and women